Cover Image. Issue 2 (24th April 2019) - Huang, Wenwei; Chen, Yin; Chen, Lanxi; Zhong, Jinshuang; Johri, Amer M.; Zhou, Jianhua
Abstract : The cover image is based on the Original Article Multimodality imaging‐guided local injection of eccentric magnetic microcapsules with electromagnetically controlled drug release by Wenwei Huang et al., https://doi.org/10.1002/cnr2.1154 . Design Credit: Wenwei Huang.